The philosophy of Qi : the Record of great doubts - Kaibara, Ekiken, 1630-1714 (Translations from the Asian classics., 2007)
Kaibara Ekken (1630-1714) was a prominent Japanese scholar who spread Neo-Confucian ideas and moral teachings throughout Japan. He was also known as the ""Aristotle of Japan"" for his studies of the natural world. Of his many writings, The Record of Great Doubts is the culmination of a lifetime of seeking a unified view of humans and nature. The text represents one of the central reflections in East Asian thought on the significance of qi ch'i, the material force coursing through all life, and is available here for the first time in English with a comprehensive introduc.